Frankenstein - Shelley, Mary (Saga Egmont, 2024)
Botched, banished, and broken, Victor Frankenstein’s creature is rejected by all mankind. But what happens when man decides to give life – and take responsibility- for a new being? There are consequences, casualties, and compounding revelations for Victor’s discovery. And for his decisions made along the way. ‘Frankenstein’ is the perfect read for fans of Heather Parry\'s ´Orpheus Builds a Girl´, Ottessa Moshfegh\'s ´Lapnova´, and Netflix’s gloriously gothic ‘Wednesday’ series. Celebrated for her tense and thrilling sci-fi and gothic novels, Mary Wollstonecraft Shelley (1797-1851) wrote the widely renowned novel ‘Frankenstein’. Adapted to countless films and stage plays, her work trailblazed a new horror genre across arts and culture. Shelly’s other works include ‘Falkner’, ‘Mathilda’, and ‘The Last Man’. She remains today an internationally renowned novelist and a constant presence in pop culture.